Effects of Heat Acclimation and Acclimatisation on Maximal Aerobic Capacity Compared to Exercise Alone in Both Thermoneutral and Hot Environments: A Meta-Analysis and Meta-Regression - Mark Waldron (Sports Medicine, 2021)
BackgroundHeat acclimation and acclimatisation (HA) is typically used to enhance tolerance to the heat, thereby improving performance. HA might also confer a positive adaptation to maximal oxygen consumption (VO2max), although this has been historically debated and requires clarification via meta-analysis.Objectives(1) To meta-analyse all studies (with and without control groups) that have investigated the effect of HA on VO2max adaptation in thermoneutral or hot environments; (2) Conduct meta-regressions to establish the moderating effect of selected variables on VO2max adaptation following HA.MethodsA search was performed using various databases in May 2020. The studies were screened using search criteria for eligibility. Twenty-eight peer-reviewed articles were identified for inclusion across four separate meta-analyses: (1) Thermoneutral VO2max within-participants (pre-to-post HA); (2) Hot VO2max within-participants (pre-to-post HA); (3) Thermoneutral VO2max measurement; HA vs. control groups; (4) Hot VO2max measurement, HA vs. control groups. Meta-regressions were performed for each meta-analysis based on: isothermal vs. iso-intensity programmes, days of heat exposure, HA ambient temperature (°C), heat index, HA session duration (min), ambient thermal load (HA session x ambient temperature), mean mechanical intensity (W) and the post-HA testing period (days).ResultsThe meta-analysis of pre–post differences in thermoneutral VO2max demonstrated small-to-moderate improvements in VO2max (Hedges’ g = 0.42, 95% CI 0.24–0.59, P < 0.001), whereas moderate improvements were found for the equivalent analysis of hot VO2max changes (Hedges’ g = 0.63, 95% CI 0.26–1.00, P < 0.001), which were positively moderated by the number of days post-testing (P = 0.033, β = 0.172). Meta-analysis of control vs. HA thermoneutral VO2max demonstrated a small improvement in VO2max in HA compared to control (Hedges’ g = 0.30, 95% CI 0.06–0.54, P = 0.014) and this effect was larger for the equivalent hot VO2max analysis where a higher (moderate-to-large) improvement in VO2max was found (Hedges’ g = 0.75, 95% CI 0.22–1.27, P = 0.005), with the number of HA days (P = 0.018; β = 0.291) and the ambient temperature during HA (P = 0.003; β = 0.650) positively moderating this effect.ConclusionHA can enhance VO2max adaptation in thermoneutral or hot environments, with or without control group consideration, by at least a small and up to a moderate–large amount, with the larger improvements occurring in the heat. Ambient heat, number of induction days and post-testing days can explain some of the changes in hot VO2max adaptation.